Study on Millennium Robotics, Powered by Artificial Intelligence and Cloud Engineering - Khaled Elbehiery; Hussam Elbehiery (New Approaches in Engineering Research Vol. 10, 2021)
Humans had begun a new era of automation of items and activities that were previously done manually, such as repetitious factory operations, sewing machines, painting, and more, in the early twentieth century, along with the industrial revolution. Humans were the smartest species on the planet to lead these efforts, and they did so successfully. However, success comes with unbridled hopes for the future, the age of Artificial Intelligence, which will far outstrip human capabilities. This research paper will touch base on these technologies, from the human brain project and Artificial Intelligence to industrial and self-aware robots. Technology did not look back, combining Artificial Intelligence (AI) with robotic automated systems that have moved swiftly from assisting humans to totally replacing humans, and have also become self-aware, from driverless cars through airplanes to smart cities through traffic lights. Factories run on solar panels, and if everything is working properly, it can anticipate a problem on the horizon and, as a result, will take steps to adjust or recover. “The percentage of intelligence that is not human is increasing and eventually we humans will represent a very small percentage of intelligence,” Elon Musk.